2015
DOI: 10.3892/mco.2015.613
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy following targeted therapy in oligometastatic renal cell carcinoma

Abstract: Abstract. Up to 40% of patients with renal cell carcinoma (RCC) with initially localized disease eventually develop metastasis following nephrectomy. The current standard of care for metastatic RCC (mRCC) is targeted therapy. However, complete response remains rare. A state of oligometastatic disease may exist, in which metastases are present in a limited number of locations; such cases may benefit from metastasis-directed local therapy, based on the evidence supporting resection of limited-volume metastases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Indeed, these metastatic sites were potentially accessible to a local tumoral treatment: stereotactic radiotherapy or thermoablation. Moreover, patients with oligometastatic renal RCC can achieve favorable clinical outcome, which justifies a target therapy on primitive renal tumor [17,18]. The association between preoperative metastasis and poor PFS suggests aggressive RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these metastatic sites were potentially accessible to a local tumoral treatment: stereotactic radiotherapy or thermoablation. Moreover, patients with oligometastatic renal RCC can achieve favorable clinical outcome, which justifies a target therapy on primitive renal tumor [17,18]. The association between preoperative metastasis and poor PFS suggests aggressive RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors underline the importance of the role of immunotherapy in the treatment of advanced RCC, as a fundamental part of a multimodality approach leading to a more effective response to treatment (33, 34).…”
Section: Resultsmentioning
confidence: 99%
“…Another retrospective study reported sequential therapy combined with targeted therapies followed by RT for mRCC. Only seven cases were enrolled and the response of metastatic lesions to the treatment was obvious (54). A larger-scale retrospective study involving 362 RCC BMs, of which 65% were treated with SRS combined with TKIs, reported 12-and 36-month OS rates to be 52% and 29%, respectively.…”
Section: Concurrent Sbrt and Targeted Therapy Is Tolerable And Has A Synergistic Antitumor Effect On Rccmentioning
confidence: 99%